Late gadolinium-enhanced cardiovascular magnetic resonance for predicting left ventricular reverse remodeling in dilated cardiomyopathy: A comprehensive review and meta-analysis - Yaqiong Zhou; Yuanwei Xu; Yangjie Li; Chuang Huang; Yucheng Chen (Journal of Cardiovascular Magnetic Resonance)
Background: There is currently a lack of evidence regarding the significance of late gadolinium enhancement (LGE) on cardiac magnetic resonance (CMR) in predicting left ventricular (LV) reverse remodeling (RR) in pooled data. This study aimed to evaluate the predictive value of the presence and extent of LGE for LVRR in patients with dilated cardiomyopathy (DCM). Methods: Systematic searches were conducted in PubMed, Embase, Cochrane Library, and ClinicalTrials.gov from database inception to May 21, 2024. We estimated the overall effect sizes using the Mantel-Haenszel random-effects model. Subgroup analyses, meta-regression, and sensitivity analyses were performed to investigate potential sources of heterogeneity among studies. Results: A total of 1141 patients (LGE prevalence: 49.7% (567/1141)) from 13 studies (5 prospective and 8 retrospective) were included. After a median follow-up period of 15 months, 43.5% of patients achieved LVRR. The presence of LGE predicted LVRR with a pooled odds ratio (OR) of 0.23 (95% confidence interval [CI]: 0.14–0.38, P < 0.01) with significant heterogeneity (I2 = 68%). The pooled OR for LVRR per percent increase in the extent of LGE was 0.94 (95% CI: 0.90–0.98, P < 0.01) with low heterogeneity (I2 = 19%). Subgroup analysis based on follow-up duration demonstrated that the presence of LGE was more strongly inversely associated with LVRR in <12 months follow-up (OR 0.06, 95% CI: 0.03–0.13, P < 0.01) compared to ≥12 months follow-up (OR 0.36, 95% CI: 0.24–0.54, P < 0.01). Conclusion: The presence and increase extent of LGE on CMR significantly diminish LVRR achievement in DCM patients, particularly in short-term follow-up (<12 months).